Focusing Firm Evolution: The Impact of Information Infrastructure on Market Entry by U.S. Telecommunications Companies, 1984–1998 - Williams, Charles; Mitchell, Will (Management Science, 2004)
Organization structure acts as a lens on the environment, gathering information and shaping its flow through a firm to inform managers' choices. This shaping of information flow happens through an organization's operating units, which selectively process information from the environment, and through the links between them, which pass information between units. We explore the relationship between this “information infrastructure” and firm strategy using structure and service information from the eight largest telephone service providers in the United States from 1984 to 1998. We find that firms with more units that scan areas of opportunity are more likely to enter a market, while firms with more units that scan nonfocal areas are less likely to enter the market. We also find that personnel links between units and the corporate level of the firm often constrain entry to new markets by dampening a unit's appetite for risk. Personnel links between operating units, on the other hand, can make a firm more likely to enter new markets, particularly when the cooperating units combine different sets of information. Thus, a firm's information infrastructure plays a dual role in shaping firm evolution, leading toward some paths and away from others.